Immunomodulation potential of Artemisia capillaris extract in rat splenocytes - Hyun-ji Lee,; Tamanna Zerin,; Young-hee kim,; byung-eui lee,; Ho-yeon Song, (International Journal of Phytomedicine, 2013)
The extract of Artemisia capillaris has been used as a traditional medicine for hepatitis or bilious disorder, and some recent studies have revealed its antimicrobial, antioxidant, antiobesity, anticarcinogenic, antioxidant, and anti-inflammatory potential. The current study was designed to evaluate the potential immunomodulatory effects of A. capillaris methanol extract on quiescent- and concanavalin A (Con A)-stimulated rat splenocytes. Proliferation of splenocytes was enhanced in response to the Con A mitogen but decreased significantly following A. capillaris extract treatment compared to that in the control and the Con A only treatment. A. capillaris extract at 10 µg/mL significantly reduced Con A-induced proliferation, and the expression of cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), and proinflammatory cytokines as tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6). Another proinflammatory cytokine, interferon-gamma (IFN-γ), was not significantly altered by either Con A or A. capillaris extract treatments when compared with the control. iNOS expression was largely blocked, whereas COX-2 expression was significantly down-regulated by A. capillaris extract treatment. This study was carried out to investigate the potential immunomodulatory activities of A. capillaris extract in a Con A induced immune condition to explore its potential pharmacological activity.